Business sustainability: a case study of Sinar Bekal (M) Sdn Bhd / Prescilla Nojem - Nojem, Prescilla (2011)
This paper investigates and determines the business sustainability of Sinar Bekal (M) Sdn Bhd in order to be strong in the international market and further success in future. It consists of investigating the important elements that SBSB need to understand in order to maintain its business sustainability in its business. The first element is research on the opportunity and challenges faced by SBSB and second element is to gauge the performance and achievement of SBSB in order to know whether SBSB is able to maintain its sustainability and competitive advantage. The findings presented will focus o this main issues.